2013
DOI: 10.1590/s0100-204x2013000800050
|View full text |Cite
|
Sign up to set email alerts
|

Growth and stress of dourado cultivated in cages at different stocking densities

Abstract: -The objective of this work was to evaluate the growth and the stress levels of juvenile dourado (Salminus brasiliensis) cultivated in cages. Fish stocked at densities of 15 (D15) and 30 (D30) fish per square meter were evaluated in a completely randomized design with three replicates. Fish were fed twice a day with extruded ration (42% crude protein). Density influenced only biomass and daily food intake, and glucose and lactate concentrations increased over time. D15 and D30 did not influence the growth of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…The lower AFCR of snapper at higher densities was most likely due to the effects of dominant fish, which cause subordinate fish such as sea bass to experience stress and decrease their feeding activity (Paspatis et al ). This supports the results of Braun et al () examining juvenile dourado, Salminus brasiliensis , cultivated in cages. In that study, the authors observed chronic stress with increasing stocking densities.…”
Section: Discussionsupporting
confidence: 92%
“…The lower AFCR of snapper at higher densities was most likely due to the effects of dominant fish, which cause subordinate fish such as sea bass to experience stress and decrease their feeding activity (Paspatis et al ). This supports the results of Braun et al () examining juvenile dourado, Salminus brasiliensis , cultivated in cages. In that study, the authors observed chronic stress with increasing stocking densities.…”
Section: Discussionsupporting
confidence: 92%
“…Dourado, S. brasiliensis, inhabits Paraná, Paraguay and Uruguay rivers and the basins connected to the Patos Lagoon complex (Weingartner & Zaniboni-Filho, 2010). Braun et al (2013) stored Dourado at different densities (0.81 and 1.63 kg/m 3 ) in fish cages (1 m 3 ) in the Itá reservoir and found that the different densities did not influence growth. However, the stress parameters evaluated were considered high for the species.…”
Section: Regulations and Main Species Produced In Fish Cages In Brazilmentioning
confidence: 99%
“…Considerando que, os parâmetros biométricos avaliados neste estudo não foram afetados pela dieta e as características inerentes desta secreção láctea, há indicativos para o uso desta fonte alimentar na alimentação de dourados juvenis. Apesar de existirem estudos utilizando o dourado nas diversas áreas da produção, como nutrição, comportamento, fisiologia e manejo, as pesquisas ainda são incipientes DAIRIKI;BRAGA et al, 2007;BRAUN et al, 2010BRAUN et al, , 2013. Com isso, as informações contidas neste trabalho podem ser de grande valia para a produção de dourados em sistema intensivo.…”
Section: Concentração De Proteína Total Dna E Rna Total Nos Tecidos unclassified